WAWASAN BARU KAJIAN NÄ€SIKH-MANSÅªKH: ANALISIS PEMIKIRAN MAá¸¥MÅ«D á¹¬ÄHÄ DAN ABDULLAHI AHMED AN-NAIM - Anshori, Muhammad (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
This paper attempts to analyze one of the main topics in the ?Ul?m Al-Qur?n (Quranic Sciences), namely n?sikh and mans?kh or theory of abrogation. The study of this concept is very important for an interpreter to avoid mistakes in understanding the verses of the Qur'an. In general, classical scholars understand the study of naskh in terms of the timing of the decline of verses makk?yah and madan?yah. The polemic between supporters and rejecters of the theory of naskh colored the literature of the Ul?m Al-Qur?n since the classical period to the present. The majority of classical scholars accepted the concept of n?sikh-mans?kh, even as a form of miracles of the Qur'an. Unlike the minority groups who did not accept the concept of n?sikh-mans?kh, for them, all the verses of the Qur'an have their respective contexts. All verses are used because there is no way the verses of the Qur'an can be ignored. However, the past naskh theory was deemed irrelevant by Ma?m?d Mu?ammad ??h? and Abdullahi Ahmed An-Naim. These two Sudanese thinkers put more emphasized on universal basic values ??contained in the verses of the Qur'an. So, it could be verses makk?yah abrogated verses madan?yah. ??h? and An-Naim want to grounded the universal teachings of Islam, and that can be found in the verses of makk?yah, not madan?yah. This is one of the unique thoughts of the two Sudan thinkers. They want to emphasized gender equality, social justice, social transformation, from reluctance to liberation. The point is that they want the basic values ??that are universal to be applied in the lives of Muslim communities, not those that are particular. The verses that contain universal basic values ??was found in the makk?yah, not the madan?yah